NILAI-NILAI SOSIAL PADA TRADISI BUKA REBO DI DANAU SIPIN KOTA JAMBI - Zalfa Shallya Faudry; Hary Soedarto Harjono; R. Imam Suwardi Wibobo; Akhyaruddin Akhyaruddin; Priyanto Priyanto (Ensiklopedia of Journal, 2023)
This study aims to describe social values in the Buka Rebo tradition.  The formulation of the problem in this study is what are the social values contained in the Buka Rebo tradition.  This research uses a qualitative ethnographic approach and content analysis method.  The research data sources used are divided into two, namely primary data sources and secondary data sources.  The primary data source in this study comes from interviews with sources from Lake Sipin who know about the Buka Rebo tradition.  Secondary data sources used in this research are theories or articles that are relevant to social valuesin the Buka Rebo tradition.The results of this study in the Buka Rebo tradition at Lake Sipin, Jambi City, are that there are three sub-social values, namely the value of compassion, the value of responsibility, and the value of harmony in life.  Affection consists of: a) devotion, (b) helping, (c) kinship, (d) loyalty, and (e) caring.  Responsibilities consist of;  (a) the value of belonging, (b) discipline, and (c) empathy, and finally the harmony of life which consists of (a) the value of justice, (b) tolerance, (c) cooperation, and (d) democracy.Keywords: Social Values, Buka Rebo Tradition